A Geomechanical Modeling Method for Shale Oil Reservoir Cluster Well Area Based on GridSearchCV - HUANG Lei; QI Yin; CHEN Weihua; DU Xianfei; MA Bing; TANG Jizhou (Cejing jishu)
In response to the challenges posed by the close proximity of Changqing shale oil well factory to water sources, forest sources, and other environmental protection zones, as well as the low efficiency and lack of geomechanical understanding in traditional well factory models, this study proposes and implements a new cluster well factory model (sectorial wells and conventional wells). Using the shale oil reservoir in block H as a case study, this research initially carries out the adjustment of reservoir physical properties and rock mechanical parameters, derived from the comprehensive analysis of well logging data. Subsequently, it integrates with a three-dimensional mesh Kriging interpolation model and optimize the Kriging interpolation parameters through GridSearchCV, which is a gridsearch and K-folder cross-validation method in the Scikit-learn machine learning. Finally, it establishes a three-dimensional geomechanical model considering reservoir lithofacies, physical properties, and geomechanical characteristics, and then predicts the geomechanical parameters of a certain cluster well factory. The reliability of the three-dimensional geomechanical model is validated by comparing numerical simulation results with well logging interpretation results. This study is a rapid and efficient geomechanical modeling method to optimize the data required for fracturing site operations.